Perfil de suscetibilidade, genes de resistência aos aminoglicosídeos e similaridade genética em amostras de Acinetobacter baumannii isoladas em um Hospital Terciário - Mataruco, Mayra Mioto [UNESP] (2015)
Acinetobacter baumannii is found in nosocomial infections, causing ventilator-associated pneumonia, bacteremia, urinary tract infections and secondary meningitis. In recent years, the extensive use of antibiotics in hospitals has contributed to the rise and emergence of A. baumannii strains resistant to a wide range of antimicrobials, including carbapenems, main antibiotics recommended on treatment. In this context, aminoglycosides gain importance as therapeutic options. Resistance to aminoglycosides is mainly due to the Aminoglycoside Modifying Enzymes (AMEs) and 16S rRNA Methylases production. In Brazil, high infection rates to carbapenem-resistant A. baumannii are observated, however information about aminoglycoside susceptibility profile and occurance of this genes are scarce. Thus, it is essential to identify resistance mechanisms and potential reservoirs, as well as perform comparison of isolates to control the spread of A. baumannii in the hospital environment. This study aimed to evaluate and compare the antimicrobial susceptibility profile, genes of aminoglycoside modifying enzymes and 16S rRNA Methylases and genetic similarity among A. baumannii isolates with clinical importance at Hospital de Base (HB) in São José do Rio Preto, SP. Additionally, the results were compared to another previous study achieved in the same hospital. 32 isolates collected between December 2013 and May 2014 were evaluated. Specie identification was performed using automated methodology and confirmed by Duplex- PCR. The susceptibility tests were the result of automated and disc-diffusion tests - for aminoglycosides Amikacin (AK), Gentamicin (CN), Tobramycin (TOB) and Kanamycin (K) - according to CLSI, 2014 and FDA, 2013. Specific primers and Multiplex-PCR were used in AMEs' and 16S rRNA Methylases' genes detection and primers REP1-REP2 were used in molecular typing by REP-PCR. All the isolates of this study...